Anomalous dental morphology and root resorption during orthodontic treatment: a pilot study - Thongudomporn Udom; Freer Terrence J (Sciendo, 1998)
The present study investigated the relation between anomalous dental morphology and root resorption during orthodontic treatment. One hundred and eleven sets of orthodontic records (a total of 1,630 teeth) were examined. Root resorption was determined from post-treatment panoramie radiographs using a five-grade quantitative measurement. It was found that patients with short or blunt roots before treatment underwent significant root shortening during or thodontic treatment. Patients with any one dental anomaly had a significantly higher degree of root resorption compared with patients with no dental anomaly. Invaginated teeth, teeth with thin or pipette-shaped roots and teeth with short or blunt roots were likely to be more susceptible to root resorption than those without such anomalies. Possible linkages between the aetiological factors of dental anomalies and the susceptibility to root resorption were discussed. The presence of anomalous dental morphology should be taken into account in or thodontic treatment planning.